Odpowiedzi

2009-11-23T22:42:27+01:00
A) (8x+16)=32
8x=32-16
8x=16
x=16:8
x=2

b) 3(2x-3)-20=4
6x-9-20=4
6x=4+29
6x=33
x=33:6
x=5,5

c) (5-4x)<_6
-4x<_6-5
-4x<_1
x>_ -1/4

d) (6x+4)<-2
6x<-2-4
6x<-6
x<-1
2009-11-23T22:44:00+01:00
A) (8x+16)=32
8x+16=32
8x=32-16
8x=16 / :2
x= 2

b) 3(2x-3)-20=4

6x-9-20 = 4
6x - 29=4
6x=4 +29
6x = 33
x = 33/6 = 11/2

c) (5-4x)<-6
5-4x<-6
-4x<-6-5
-4x<-11
x> 11/4

d) (6x+4)<-2
6x+4 < -2
6x <-2-4
6x<-6
x<-1
Najlepsza Odpowiedź!
2009-11-23T22:44:15+01:00
A) (8x+16)=32
8x+16=32 |-16
8x=16 |:8
x=2

b) 3(2x-3)-20=4
6x-9-20=4
6x-29=4 |+29
6x=33 |6
x=5,5

c) (5-4x)<-6
5-4x<-6 |-5
-4x<-11
4x=11 |:4
x=2,75

d) (6x+4)<-2
6x+4<-2 |-4
6x<-6 |:6
x<-1